A história de vida de professor na interface sobre a gestão democrática: em um estudo autobiográfico - GUEDES, Ivonete Maria Sobreira (2019)
This paper aims to narrate my experiences as a teacher of Basic Education in the rural school in themunicipalityof Castanhal in the interface on democratic management. The present text discusses the history of life; personal, professional and academic interface in the discussions on school management. These discussions point to education as an area of socio-educational character that conglomerates several participants within this school context, interconnect diverse types of people each with their designation and professional performance. Given this panorama, it is appropriate to remember that relationships arise as a work of a human process, through the result of people acting. importance of community participation in school management. This theme was based on bibliographical research elucidating the importance of democratic management in the school context in the interface with the experiences, in the condition of teaching, occurred during fifteen years. The democratic management in the school context is of paramount importance, giving visibility to the actions of the school and thus optimizing the social function of the same. A comprehensive school and having the role of agent transformation. Our society goes through remarkable moments where democracy has put it in check. In this scenario, the school as an institution that forms critical citizens could not fail to position critically in relation to these issues that are put, among other points, to minimize the importance of institutions, including those forged to deal directly with human formation. Through participatory and effective democratic management, it is possible to ensure that the school space is strengthened in order to guarantee the necessary human training so that the countryside and the city can produce other realities, less authoritarian and exclusive.